'Aorta code' implementation and preliminary results of a multidisciplinary protocol for patients with acute aortic syndrome. (25th November 2020) - Ferrera Duran, C; Vilacosta, I; Perez-Villacastin, J; Busca, P; Carrero, A; Martin Martinez, A; Martin Sanchez, F.J; Dominguez Garcia, M.J; Martinez, I; Cobiella, J; Viana Tejedor, A; Cortes Martinez, A; et al.
Abstract: Background: Expediting life-saving care for patients with acute aortic syndrome (AAS) through multi-disciplinary code protocols is a potential method to improve outcomes. Other code protocols for cardiovascular emergencies, such as ST-elevation myocardial infarction and stroke have shown excellent results. Aim: To examine the implementation and preliminary results of a code protocol "Aorta Code" for patients with AAS in a healthcare framework of a 4-hospital network in our city by reviewing the number of patients detected, patient's transference time, aortic surgery and patient's outcome during a trial period of 10 months (April 2019-January 2020). A comparison with a previous 2-year period with standard of care management of AAS was performed. Methods: "Aorta Code" uses a specific diagnostic algorithm to improve detection of patients with AAS at the emergency room, facilitates their quick transfer to the referral hospital by activating a paging system, and places acute cardiovascular care unit, operating room and surgeons specialized in aortic pathology on standby. Results: Compared to a previous 2-year period (2017–2018) (group I), the current implementation of "Aorta Code" in a period of 10 months (group II) in our 4-hospital network involving the healthcare of 1.100000 inhabitants resulted in the detection of more patients with AAS (group-I: n=18 patients (0.8 patients/month), group-II: n=19 patients (1.9 patients/month); p=0.013). AAS detection in secondary hospitals importantly increased (33.3% vs 63.8%, p=0.07). The "Aorta Code" achieved a significant decrease in patient's transference time to referral hospital (group-I: median 259 min (IQR 150–1911), group-II: median 129 min (IQR 95.5–167.25); p=0.035). There was a marked reduction in the number of surgeons involved in the "Aorta Code" (group-I= 7 cardiac, 6 vascular, group-II= 2 cardiac, 2 vascular). Thirty-day mortality was lower in group-II in the whole AAS cohort (group-I= 22.2%, group-II= 12.5%; p=0.660) and in type A AAS (28.6% vs 18.2%, p=0.661). Misdiagnosis rate (false-calls): 11 patients (7 of them with non-acute aortic disease). Conclusion: "Aorta Code" facilitates detecting patients with AAS at the emergency room, speeds them to the referral hospital center, allows patients to be treated by surgeons specialized in aortic surgery and improves patient's outcome. Further prospective studies examining the utility of "Aorta Code" are warranted. Funding Acknowledgement: Type of funding source: None